Your Father's a Fighter; Your Daughter's a Vegetable: A Critical Analysis of the Use of Metaphor in Clinical Practice. Issue 5 (23rd October 2020) - Tate, Tyler
Abstract: There are two widespread beliefs about the use of metaphors in clinical medicine. The first is that military metaphors are harmful to patients and should be discouraged in medical practice. The second is that the metaphors of clinical practice can be judged by and standardized in reference to neutral criteria. In this article, I evaluate both these beliefs, exposing their shared flawed logic. This logic underwrites the false empiricist assumptions that metaphorical language and literal language are fundamentally distinct, play separate roles in communication, and therefore can be independently analyzed, systematized, and prescribed. Next, using the resources of ordinary language philosophy, I lay out a theoretical view of medical metaphors that is grounded in metaphor use within clinician‐patient relationships. Finally, drawing on the work of philosopher Max Black, I diagram a practical conceptual framework for clinicians to use when they consider whether a metaphor is appropriate for a specific patient encounter .